Soil microbial community dynamics in response to cover crop implementation and P fertilizer management - Stewart, Catherine Louise (Kansas State University, 2021)
Soil microorganisms facilitate nutrient cycling within soils providing a critical component of soil health and serve a key role in maintaining productive agricultural systems. There are many ways to assess soil health and how soil systems respond to agricultural management practices. Some of these methods target either recalcitrant or labile nutrient pools within soils, while others focus on the microorganisms themselves. This study sought to examine a variety of different assays targeting components of soil health and how they were impacted by agricultural management practices. Objectives of this study were to (i) examine carbon (C) and nitrogen (N) soil health metrics; (ii) to explore the microbial community structure using phospholipid fatty acid analysis, and (iii) to identify key microbial functional gene composition, and soil health metrics relate to key soil microbial functional gene composition in the fall 2019 and spring 2020 seasons in response to management practices that include cover crop usage and P fertilizer treatments at an early transition to no-tillage (less than 5 years) site at the Kansas Agricultural Watershed Field Research Facility. Objective one examined soil samples from the spring and fall of 2018 and 2019 at the 0-5 cm soil depth. Objective two examined soil samples from the spring and fall of 2018 and 2019 at the 0-5, 5-10, and 10-15 cm depths. Objective three examined soil samples from fall 2019 and spring 2020 at the 0-5 cm depth. The experiment has a 2 by 3 factorial treatment structure with two levels of cover crop treatments: with cover crops (CC) and without cover crops (NC) and three levels of P fertilizer managements: no P fertilizer (NP), fall broadcast (FB), and spring injected (SI) in a randomized complete block design with three replicates of each treatment combination. When assessing traditional soil health assays, I found assays that targeted soil C nutrient pools were more consistently able to detect differences with the cover crop implementation as compared to those that examined N pools. Assays using total C, microbial biomass C, active C, dissolved organic C, and enzyme activity were more successful in detecting cover crop implementation as compared to assays that targeted N pools including total N, microbial biomass N, dissolved organic N, and inorganic N. For the second objective I found that PLFA microbial biomass decreases with increasing depth, and that cover crops can significantly increase microbial biomass in several PLFA categories when compared to plots with no cover crop in a no-tillage system with a corn-soybean rotation. The microbial community composition was found to be similar between the CC and NC treatments at the 0-5 cm depth. Bacteria and fungi were not impacted by treatments. The third objective found that genes related to microorganismal nutrient dynamics responded differently based on seasonality with fall samples being more frequently responsive to treatment differences than spring samples. This objective found the greatest gene abundance in the NP*CC treatment in fall within the examined sub-categories of microorganism functional genes.
Keywords: Soil microorganisms; Soil science; Phospholipid fatty acid (PLFA); GeoChip